Instruments to promote trade between countries: the case of Portugal - Ribeiro, Sandra (2022)
International trade is playing an increasingly important role in the economic growth and competitiveness of an economy. Thus, it is one of the engines of countries' development. The opening of economies and the phenomenon of globalisation have intensified business at international level. There are many factors that encourage trade at an international level and others that constitute barriers to the normal functioning of the commercial exchange process between countries. Although there are many factors that encourage cross-border trade, there are still some obstacles that act as a barrier and should be eliminated, such as economic, political, linguistic or geographic. For this study, and in line with several authors, is used the most widely used econometric tool to study international trade, i.e., the gravity model. This model has been used since the 1960s, initially by Tinbergen (1962), but subsequently improved over the years and expanded with several variables that intend to explain trade flows between two countries. This model is used to explain trade flows between two countries. Considering initially that exports between two countries are positively associated with the size of the two economies and negatively related to factors that indicate the existence of barriers to trade, giving greater emphasis to the existing distance between countries. Besides this model, this paper uses the BIPLOT analysis is a multivariate technique proposed by Gabriel (1971) which has the main objective of performing an approximated graphical representation, with reduced dimension, of a data matrix Xnxp. It is done in such a way that the representation allows the visualization in the same plane of the relations and interrelations between rows and columns of matrix X, considering the same type of variable as the previous model. With the use of this methodology, it is concluded about the relationship between EU membership and linguistic affinity with exports is important to characterize the reality of Portuguese exports, going beyond the geographical distance and the GDP of the destination countries and that language barriers can impose significant costs on bilateral trade between countries that do not share some sort of common spoken language, either official or acquired foreign languages. It’s observed a decrease in trade with a country due to increase in distance, what substantiate the ideas underlying the gravitational model. The relationship between EU membership and linguistic affinity with exports is important to characterize the reality of Portuguese exports, going beyond the geographical distance and the GDP of the destination countries.